Предмет: Алгебра,
автор: lera12345678910134
упростите выражение
(x-3)(x-7)-2x(3x-5)=
ПРОШУ! СРОЧНО
Ответы
Автор ответа:
1
Ответ:
(x-3)(x-7)-2x(3x-5)=(x²-7x-3x+21)-(6x²+10x)=x²-10x+21-6x²-10x=-5x²+21
Объяснение:
lera12345678910134:
спасибо) а можешь помочь ещё упростить? я вопрос задавала
Автор ответа:
2
( х - 3 ) ( х - 7 ) - 2х ( 3х - 5 ) =
х² - 7х - 3х + 21 - 6х² + 10х =
-5х² + 21 ;
Удачи ) )
Похожие вопросы
Предмет: Литература,
автор: yaivazova
Предмет: Математика,
автор: lizzyprincess
Предмет: Математика,
автор: muratbaevazupar
Предмет: Химия,
автор: Аноним
Предмет: Литература,
автор: vldadaivanova